Chapter Throughput Analysis of Wireless Sensor Networks via Evaluation of Connectivity and MAC Performance - Buratti, Chiara; Fabbri, Flavio (InTechOpen, 2011)
Computer networking & communications
English
Keywords: Computer networking & communications; Computing & information technology